Engineered acellular collagen scaffold for endogenous cell guidance, a novel approach in urethral regeneration. (1st October 2016) - Pinnagoda, Kalitha; Larsson, Hans M.; Vythilingam, Ganesh; Vardar, Elif; Engelhardt, Eva-Maria; Thambidorai, Rajendrarao C.; Hubbell, Jeffrey A.; Frey, Peter
Graphical abstract: Abstract: The treatment of congenital malformations or injuries of the urethra using existing autologous tissues can be associated with post-operative complications. Using rat-tail collagen, we have engineered an acellular high-density collagen tube. These tubes were made of 2 layers and they could sustain greater burst pressures than the monolayered tubes. Although it remains a weak material this 2 layered tube could be sutured to the native urethra. In 20 male New Zealand white rabbits, 2 cm long grafts were sutured in place after subtotal excision of the urethra. This long-term study was performed in Lausanne (Switzerland) and in Kuala Lumpur (Malaysia). No catheter was placed post-operatively. All rabbits survived the surgical implantation. The animals were evaluated at 1, 3, 6, and 9 months by contrast voiding cysto-urethrography, histological examination and immunohistochemistry. Spontaneous re-population of urothelial and smooth muscle cells on all grafts was demonstrated. Cellular organization increased with time, however, 20% of both fistula and stenosis could be observed post-operatively. This off-the shelf scaffold with a promising urethral regeneration has a potential for clinical application. Statement of Significance: In this study we have tissue engineered a novel cell free tubular collagen based scaffold and used it as a urethral graft in a rabbit model. The novelty of our technique is that the tube can be sutured. Testing showed better burst pressures and the grafts could then be successfully implanted after a urethral excision. This long term study demonstrated excellent biocompatibility of the 2 cm graft and gradual regeneration with time, challenging the current literature. Finally, the main impact is that we describe an off-the-shelf and cost-effective product with comparable surgical outcome to the cellular grafts.